Quality Management at Sekolah Penggerak Based on Islamic Boarding School System in Enhancing Student Achievement: A Literature Review - Ahmad Sirojul Munir; Teguh Triwiyanto; Rochmawati (Yayasan Ilomata, 2026)
This study explores the implementation of quality management in Sekolah Penggerak schools based on the pesantren (Islamic boarding school) system and its potential contribution to student learning outcomes at the secondary education level. Using a systematic literature review, the study synthesizes evidence from previous research to identify patterns in how quality management practices are applied within pesantren-based schools. Four key thematic areas emerged: transformational leadership of school principals, integration of pesantren values into the curriculum, ongoing monitoring and evaluation of educational processes, and teacher professional development programs. Transformational leadership was frequently associated with supportive and motivating school environments, while the integration of pesantren values emphasized moral, ethical, and spiritual formation alongside academic learning. Continuous quality management practices, including assessment and feedback mechanisms, were highlighted as common strategies for improving instructional quality. The review also identified challenges such as limited infrastructure, human resource constraints, and variability in stakeholder engagement. These findings suggest that adopting structured, value-informed quality management practices may support holistic student development and provide insights for blended religious-secular educational reforms. The study underscores the importance of collaborative approaches among educators, students, parents, and communities in sustaining quality improvement.